The regional dimension of sectoral innovativeness: An empirical investigation of two specialised supplier and two science-based industries - Matthias Bürger; Uwe Cantner (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
The aim of this paper is to test how geographical and technological proximity relate to a particular industry's innovative output. Two mechanisms are therefore tested, i.e. agglomeration economies and the regional exploitation of technological proximity. A new dataset is applied, which includes German patent applications from within the period 1995 to 2006. Four industries are considered, two of which are science-based, whereas the remaining two are specialised supplier industries. While diversity is associated with high innovative output in the specialised supplier industries, the results for specialisation are mixed. However, all industries seem to benefit, at least to a certain degree, from the regional re-combination of their own technologies with those of specific key industries.
Keywords: O18; R11; 330; Innovation; Proximity; Diversity; Innovation; Verarbeitendes Gewerbe; Regionale Arbeitsteilung; Technologie; Regionale Konzentration; Schätzung; Hochtechnologiesektor; Lieferant; Deutschland